The cottage garment industry of barangay San Juan, Taytay a situationer - Diaz, Dorothy Dame C.; Arribas, Lyda Boquiren (1999.)
The Cottage Garment Industry of Taytay has existed for more than a hundred years now. Inspite of this long period of time, it seemed not to have improved much its impact on the entire municipality. It still remains a cottage industry. This study therefore was aimed to conduct an inquiry about the real situation, identify the problems and the causes and effects, and to finally develop some recommendations for growth and development. The analysis was made on four factors, namely: Management and Human Resource, Marketing, Financial Management, and Production. Due to time and financial constraints, the study was limited ti Brgy. San Juan which is the biggest barangay and which is also locale of most garment manufacturing businesses in the municipality. The study showed that the said industry has neglected the organization of business and and manufacturing operations. No planning has been employed and business has been conducted in a day-to0day, short term basis. As a result, a lot of inefficiencies tie down the businesses and limit growth and development. There is an urgent need to restructure their business practices. An effective marketing strategy needs to be employed to assure excellent sales performance. Other business elements also need to be organized and managed efficiently to meet the demands of the garment industry.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines -- Rizal